CuO / ZrO2 catalyst for hydrogen production by methanol reforming as well as preparation method and application of CuO / ZrO2 catalyst
By loading single-clinical CuO on the ZrO2 support and preparing the catalyst by co-precipitation and impregnation methods, the problem of insufficient stability of copper-based catalysts in long-term use is solved, and more efficient hydrogen production performance of methanol water vapor reforming is achieved, and production costs and environmental impacts are reduced.
Patent Information
- Application Number
- CN202510030640.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-01
AI Technical Summary
Existing copper-based catalysts are prone to sintering and inactivation effects in long-term working environments, resulting in a decrease in hydrogen production performance, and catalysts with ZnO or CeO2 as support have shortcomings in stability and low-temperature reaction performance.
The CuO/ZrO2 catalyst supported by the single-climb phase CuO was prepared by co-precipitation method and impregnation method. The single-climb phase ZrO2 was used as a support to optimize the dispersion threshold of CuO by XRD extrapolation method to improve the stability and activity of the catalyst.
It improves the stability of the catalyst and the performance of hydrogen production by methanol water vapor reforming, reduces the cost of raw materials and preparation complexity, and does not have secondary pollution to the environment.
Smart Images

Figure CN119733511A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy catalysis and relates to a method for preparing a CuO / ZrO2 catalyst for hydrogen production by methanol reforming. Background Art
[0002] Hydrogen energy has the advantages of low carbon, high efficiency, safety and controllability, and is widely used in many fields such as industry, transportation, construction and power systems. The development and utilization of hydrogen energy can effectively alleviate the environmental pollution caused by fossil energy (BE Lebrouhi, JJ Djoupo, B. Lamrani, K. Benabdelaziz, T. Kousksou, Global hydrogen development - A technological and geopolitical overview, Int. J. Hydrog. Energy 47 (2022) 7016–7048.). However, considering the obstacles such as hydrogen storage and transportation, it is still difficult to achieve pure hydrogen combustion in most vehicles. Fuel cells are currently mainly proton exchange membrane fuel cells (PEMFC), which have the advantages of low operating temperature and fast startup, and are very suitable for the transportation field. In order to achieve a safe and convenient PEMFC hydrogen supply chain, on-board hydrogen supply methods such as reforming of hydrogen-rich fuels (such as methanol steam reforming for hydrogen production, MTSR) have attracted increasing attention (X. Tang, Y. Wu, Z. Fang, X. Dong, Z. Du, B. Deng, C. Sun, F. Zhou, X.Qiao, X. Li, Syntheses, catalytic performances and DFT investigations: A recent review of copper-based catalysts of methanol steam reforming for hydrogen production, Energy 295 (2024) 131091.).
[0003] For decades, there have been many studies on MTSR catalysts, which are mainly divided into two categories: copper-based catalysts and precious metal catalysts such as Pt and Pd (N. Iwasa, T. Mayanagi, W. Nomura, M. Arai, N. Takezawa, Effect of Znaddition to supported Pd catalysts in the steam reforming of methanol, Appl. Catal. -Gen. 248 (2003) 153–160.). Copper-based catalysts have the advantages of high methanol conversion rate, high hydrogen production rate in medium and low temperature zones, simple synthesis, and low cost, and are widely used in industrial MTSR hydrogen production. However, under long-term working conditions, the copper phase usually has severe sintering and deactivation effects, which may have irreversible effects on hydrogen production performance. At the reaction temperature, carbon deposition will further endanger the stability of copper-based catalysts.
[0004] According to the different carriers, the pure oxide carriers that have been studied more are mainly ZnO, CeO2, ZrO2, etc. Among them, for catalysts with ZnO as the carrier, Nakamura et al. (J. Nakamura, Y. Choi, T. Fujitani, On the Issue ofthe Active Site and the Role of ZnO in Cu / ZnO Methanol Synthesis Catalysts, Top. Catal. 22 (2003) 277–285) believe that the formation of Cu-Zn alloy is one of the reasons why Cu-Zn catalysts have high activity. The main function of ZnO is to generate a stable surface alloy phase, which can be determined by the XRD spectrum, that is, part of the ZnO component is mixed with Cu particles, and then alloying occurs between the two phases. However, catalysts with ZnO as the carrier often have poor stability, mainly due to high-temperature Cu sintering. The high activity of the Cu / CeO2 system is attributed to its unique redox properties, which has been a hot topic in recent years. Taghizadeh et al. (M. Taghizadeh, H. Akhoundzadeh, A.Rezayan, M. Sadeghian, Excellent catalytic performance of 3D-mesoporous KIT-6supported Cu and Ce nanoparticles in methanol steam reforming, Int. J.Hydrog. Energy 43 (2018) 10926–10937.) found that the catalyst containing CeO2 showed higher H2 yield and CO2 selectivity, which was attributed to the redox properties of CeO2. More specifically, the valence state of CeO2 4+ and Ce 3+ Between and in Cu 2+ , Cu + and Cu 0 There is a lot of electron transfer between them. However, catalysts with CeO2 as carrier often have poor performance in low-temperature reactions. Summary of the invention
[0005] The purpose of the present invention is to provide a CuO / ZrO2 catalyst for hydrogen production from methanol reforming and its preparation method and application. The catalyst is a Cu-based catalyst with monoclinic ZrO2 as a carrier.
[0006] The CuO / ZrO2 catalyst for producing hydrogen from methanol reforming described in the present invention is characterized in that the ZrO2 carrier is monoclinic, and the catalyst is a CuO / ZrO2 catalyst loaded with monoclinic CuO.
[0007] The present invention firstly adopts a coprecipitation method to prepare a monoclinic ZrO2 carrier, and then prepares a CuO / ZrO2 catalyst loaded with monoclinic CuO by an impregnation method. The catalyst is applied to the front-end hydrogen supply system of a proton exchange membrane fuel cell loaded in a new energy vehicle.
[0008] The method for preparing a CuO / ZrO2 catalyst for producing hydrogen by reforming methanol described in the present invention is characterized by comprising the following steps.
[0009] (1) Weigh a certain amount of ZrO(NO3)2 into a beaker, heat and stir in a 90°C water bath until it is completely dissolved.
[0010] (2) Slowly add ammonia water to adjust the pH value of the solution to 12, stir and precipitate at room temperature for several hours. Then wash the precipitate with deionized water until the total soluble solids TDS in the filtrate is < 20 ppm.
[0011] (3) The product obtained in step (2) was then dried in an oven at 110° C. overnight, taken out and ground into powder.
[0012] (4) The product obtained in step (3) was calcined in a muffle furnace at 600 °C at a heating rate of 2 °C / min for 5 h to obtain a monoclinic ZrO2 carrier.
[0013] (5) Prepare x wt.% CuO / ZrO2 by impregnation method, where x = 1-5. Dissolve a certain amount of Cu(NO3)2•3H2O(AR) in ionized water, and then add the corresponding mass of the monoclinic ZrO2 carrier obtained in step (4). Stir the mixture at room temperature for 6 h, place it in a water bath at 80 °C, stir and evaporate to dryness, place it in an oven at 110 °C to completely dry it, and grind it.
[0014] (6) The product obtained in step (5) was ground and placed in a muffle furnace at 450 °C and calcined at a heating rate of 2 °C / min for 4 h to obtain catalysts with different loading amounts of 1~5% CuO / ZrO2.
[0015] The present invention uses the monolayer dispersion theory to design the catalyst. By preparing two carriers with ZrO2 crystal structures (monoclinic: m-ZrO2; tetragonal t-ZrO2), the monolayer dispersion threshold is obtained by XRD extrapolation method, and the strength of the interaction between the carrier crystal and CuO is explored, and the catalyst with the best performance is selected. The research results of the present invention show that monoclinic ZrO2 loaded with monoclinic CuO has a larger dispersion threshold, corresponding to better methanol reforming hydrogen production performance. This is conducive to the industry to select the appropriate method to prepare high-efficiency catalysts.
[0016] The present invention focuses on the influence of the carrier crystal phase on the loaded components, which is specifically reflected in that the same crystal phase is more conducive to the dispersion of the loaded components, thereby obtaining more abundant surface active sites and methanol steam reforming hydrogen production performance. Among them, the specific implementation method of the XRD extrapolation method is as follows.
[0017] By adjusting the isogradient loading amount of the active component CuO, a catalyst with isogradient active components was synthesized and characterized by obtaining its XRD spectrum. CuO / I ZrO2 Ratio and per 100m 2 The amount of CuO loaded on the ZrO2 surface is plotted, and the relevant linear line is fitted. The dispersion threshold of CuO on the ZrO2 surface is deduced through the intersection of the straight line and the X-axis. This threshold point reflects that the dispersion threshold of CuO / m-ZrO2 is greater than that of CuO / t-ZrO2. Therefore, the test results of methanol steam reforming hydrogen production show that the three loading amounts of Cu / m-ZrO2, 1%, 3%, and 5%, are always greater than Cu / t-ZrO2.
[0018] The invention discloses a CuO / ZrO2 catalyst for producing hydrogen by reforming methanol, and its application in producing hydrogen by steam reforming methanol. The method comprises the following steps.
[0019] 100 mg of catalyst of 40-60 mesh was placed in the reactor, and a 10 vol% H2 / Ar mixed gas with a flow rate of 30 mL / min was introduced for reduction for 40 min at 1 atm and 300 °C. The reaction temperature was controlled at 200-360 °C by a thermocouple. A mixture of H2O and CH3OH with a CH3OH / H2O molar ratio of 1 / 1.5 and a flow rate of 0.05 mL / min was injected into the vaporization chamber by a micro pump, and the temperature was controlled at 200 °C to completely evaporate the liquid into gas. The corresponding reaction space velocity (WHSV) was 42000 mL / h·g cat Then, Ar was introduced into the reactor at a flow rate of 30 mL / min for reaction.
[0020] The present invention constructs two different crystal phases of ZrO2. Based on the "similar phase dispersion" theory, in order to design a more efficient methanol steam reforming catalyst, CuO / ZrO2 catalysts with different CuO loadings of equal gradients are prepared, and the physical and chemical properties of the monoclinic CuO catalyst on the monoclinic ZrO2 and tetragonal ZrO2 are studied. When the same loading amount of monoclinic CuO is on a monoclinic ZrO2 carrier, the catalytic activity is higher than that on a tetragonal ZrO2 carrier. It is found that when the crystal phase structure between the loaded metal oxide and the carrier is the same, the carrier is more conducive to the dispersion of the active components, and there is a "similar phase dispersion" phenomenon, which is the essential reason for the performance difference. Therefore, the present invention has guiding significance for the rational design of efficient MTSR catalysts.
[0021] Compared with the prior art, the catalyst prepared by the present invention has the following advantages.
[0022] (1) The raw material cost for preparing the catalyst of the present invention is low, the preparation process is simple and easy, the equipment requirements are low, the solvent is non-toxic and harmless, and there is no secondary pollution to the environment.
[0023] (2) The coprecipitation method, sol-gel method and impregnation method used in the present invention for preparing the catalyst have simple and easy preparation processes and the reaction process is easy to control.
[0024] (3) In the methanol steam reforming hydrogen production reaction, a Cu-based catalyst prepared by the present invention with different crystalline phases of ZrO2 as the carrier is used to measure the monolayer dispersion threshold of monoclinic CuO on monoclinic ZrO2 and tetragonal ZrO2 using the XRD extrapolation method. XPS, H2-TPR and N2O titration and other characterizations are used to prove that the catalytic activity of monoclinic CuO on the monoclinic ZrO2 carrier is higher than that on the tetragonal ZrO2 carrier with the same loading amount. By regulating the crystalline phase structure of the carrier and the active component, a more efficient methanol steam reforming hydrogen production catalyst can be designed. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the X-ray diffraction (XRD) crystal phase structure analysis spectrum of the catalyst x wt.% CuO / m-ZrO2 obtained in Example 1.
[0026] Figure 2 The prepared in Example 1 Figure 1 The monolayer dispersion threshold fitting curve obtained by quantification of XRD spectrum.
[0027] Figure 3 This is the X-ray diffraction (XRD) crystal phase structure analysis spectrum of the catalyst x wt.% CuO / t-ZrO2 obtained in Comparative Example 1.
[0028] Figure 4 The comparative example 1 obtained Figure 3Monolayer dispersion threshold fitting curve quantified from XRD spectrum.
[0029] Figure 5 XPS Cu 2p spectra of the catalysts obtained in Example 1 and Comparative Example 1 (x=1%, 3%, 5%).
[0030] Figure 6 H2-TPR graphs measured for the catalysts obtained in Example 1 and Comparative Example 1 (x=1%, 3%, 5%).
[0031] Figure 7 This is a test chart of the methanol steam reforming hydrogen production performance of the 1% CuO / ZrO2 catalyst samples obtained in Example 1 and Comparative Example 1.
[0032] Figure 8 This is a test chart of the methanol steam reforming hydrogen production performance of the 3% CuO / ZrO2 catalyst samples obtained in Example 1 and Comparative Example 1.
[0033] Fig. 9 This is a test chart of the methanol steam reforming hydrogen production performance of the 5% CuO / ZrO2 catalyst samples obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. Example 1
[0035] The method for preparing a CuO / ZrO2 catalyst for hydrogen production from methanol reforming described in this embodiment (CuO loaded on monoclinic ZrO2) comprises the following steps.
[0036] (1) The monoclinic ZrO2 carrier was synthesized by coprecipitation method. ZrO(NO3)2 was dissolved in a certain amount of deionized water and heated and stirred in a water bath at 90°C until it was completely dissolved.
[0037] (2) Slowly add ammonia water to adjust the pH value of the solution to 12, stir and precipitate at room temperature for several hours. Then wash the precipitate with deionized water until the total soluble solids TDS in the filtrate is <20 ppm.
[0038] (3) The obtained product was dried in an oven at 110 °C overnight, ground and calcined in a muffle furnace at 600 °C for 5 h at a heating rate of 2 °C / min to obtain the final product, a monoclinic ZrO2 carrier.
[0039] (4) x wt.% CuO / ZrO2 (x = 1, 3, 5, 7, 9, 11, 13) was prepared by impregnation method. A certain amount of Cu(NO3)2•3H2O(AR) was dissolved in deionized water and then the corresponding mass of monoclinic ZrO2 carrier was added.
[0040] (5) The mixture was stirred at room temperature for 6 h, then placed in a water bath at 80 °C and stirred to dryness, placed in an oven at 110 °C to completely dry and grind, and placed in a muffle furnace at 450 °C and calcined at a heating rate of 2 °C / min for 4 h. The resulting catalysts were named 1% CuO / ZrO2, 3% CuO / ZrO2, 5% CuO / ZrO2, 7% CuO / ZrO2, 9% CuO / ZrO2, 11% CuO / ZrO2, and 13% CuO / ZrO2 according to their loading amounts.
[0041] A series of catalysts prepared in Example 1 were synthesized by adjusting the isogradient loading amount of the active component CuO using the XRD extrapolation method, and the catalysts with isogradient active components were characterized and their XRD spectra were obtained. CuO / I ZrO2 The ratio is plotted against the amount of CuO loaded on the ZrO2 surface per 100 m2, and a related linear straight line is fitted. The dispersion threshold of CuO on the ZrO2 surface is deduced from the intersection of the straight line and the X-axis.
[0042] Comparative example 1.
[0043] The preparation method of a CuO / ZrO2 catalyst for hydrogen production from methanol reforming described in this comparative example (CuO loaded on tetragonal ZrO2) comprises the following steps.
[0044] (1) Weigh a certain amount of Zr(NO3)4•5H2O and dissolve it in a certain amount of deionized water. Add citric acid in a molar ratio of Zr:citric acid of 1:1.2. Add deionized water at room temperature and continue stirring until all the solution is dissolved.
[0045] (2) Place the beaker in a 90°C water bath and stir and evaporate until the mixture becomes a gel.
[0046] (3) Place the product in an oven at 110 °C and dry overnight. Then, ignite the product at 300 °C to obtain a black solid which is then ground.
[0047] (4) The product obtained in step (3) was placed in a muffle furnace at 400 °C and calcined at a heating rate of 2 °C / min for 4 h to obtain a final product, a tetragonal ZrO2 carrier.
[0048] (5) Prepare x wt.% CuO / ZrO2 (x = 1, 3, 5, 7, 9, 11, 13) by impregnation method. Dissolve a certain amount of Cu(NO3)2•3H2O(AR) in deionized water and add the corresponding mass of the support obtained in step (4). Stir the mixture at room temperature for 6 h, place it in a water bath at 80 °C and evaporate it to dryness, place it in an oven at 110 °C to completely dry it and grind it.
[0049] (6) The product obtained in step (5) was ground and then placed in a muffle furnace at 450 °C for calcination at a heating rate of 2 °C / min for 4 h. The catalysts finally obtained were named 1% CuO / ZrO2, 3% CuO / ZrO2, 5% CuO / ZrO2, 7% CuO / ZrO2, 9% CuO / ZrO2, 11% CuO / ZrO2, and 13% CuO / ZrO2 according to the loading amount.
[0050] A series of catalysts were prepared in Comparative Example 1. The catalysts with equal mass gradient active components were synthesized by adjusting the equal gradient loading amount of the active component CuO using the XRD extrapolation method. The XRD spectra were characterized and the catalysts were tested. CuO / I ZrO2 The ratio is plotted against the amount of CuO loaded on the ZrO2 surface per 100 m2, and a related linear straight line is fitted. The dispersion threshold of CuO on the ZrO2 surface is deduced from the intersection of the straight line and the X-axis. Example 2
[0051] A series of catalysts prepared in Example 1 and Comparative Example 1 were characterized by XPS. The x-ray photon spectra (XPS) of the samples were obtained on a PHI-5000C ESCA device upgraded by RBD, with an irradiation source of Mg Kα (250 W, 14 kV). BE calibration was performed based on the standard c1s signal with a binding energy of 284.6 eV. The CuO dispersion was analyzed by comparing the ratio of the CuO XPS integral area, and the XPS spectrum was drawn. Example 3
[0052] A series of catalysts prepared in Example 1 and Comparative Example 1 were characterized by H2-TPR, and 50 mg of the catalyst was used for the test. Prior to the experiment, the catalyst was pretreated in a high-purity gas flow at 400°C for 30 min to remove preformed surface carbonates and any possible impurities. After purging with an ultra-high purity Ar gas flow at room temperature for 30 minutes, the temperature was raised from room temperature to 400°C at a heating rate of 10°C / min in a 10% H2 / Ar mixture of 30 mL / min. A thermal conductivity detector (TCD) was used to monitor the consumption of H2. The hydrogen consumption was quantified using a 99.99% CuO sample as a standard. Example 4
[0053] The 1% CuO / ZrO2 catalysts prepared in Example 1 and Comparative Example 1 were subjected to a catalyst MTSR performance test. 100 mg of 1% CuO / ZrO2 catalysts of 40-60 mesh were placed in a reactor, and a 10 vol% H2 / Ar mixed gas with a flow rate of 30 mL / min was introduced for reduction for 40 min at 1 atm and 300°C. The reaction temperature was controlled at 200-360°C, and the temperature was controlled by a thermocouple. A mixture of H2O and CH3OH with a CH3OH / H2O molar ratio of 1 / 1.5 and a flow rate of 0.05 mL / min was injected into the vaporization chamber by a micropump, and the temperature was controlled at 200°C to completely evaporate the liquid into gas. The corresponding reaction space velocity (WHSV) was 42000 mL / h·g cat Then, Ar was introduced into the reactor at a flow rate of 30 mL / min to react. And its performance was evaluated. Example 5
[0054] The 3% CuO / ZrO2 catalysts prepared in Example 1 and Comparative Example 1 were subjected to a catalyst MTSR performance test. 100 mg of 3% CuO / ZrO2 catalysts of 40-60 mesh were placed in a reactor, and a 10 vol% H2 / Ar mixed gas with a flow rate of 30 mL / min was introduced for reduction for 40 min at 1 atm and 300°C. The reaction temperature was controlled at 200-360°C, and the temperature was controlled by a thermocouple. A mixture of H2O and CH3OH with a CH3OH / H2O molar ratio of 1 / 1.5 and a flow rate of 0.05 mL / min was injected into the vaporization chamber by a micropump, and the temperature was controlled at 200°C to completely evaporate the liquid into gas. The corresponding reaction space velocity (WHSV) was 42000 mL / h·g cat Then, Ar was introduced into the reactor at a flow rate of 30 mL / min to react. And its performance was evaluated. Example 6
[0055] The 5% CuO / ZrO2 catalysts prepared in Example 1 and Comparative Example 1 were subjected to a catalyst MTSR performance test. 100 mg of 5% CuO / ZrO2 catalysts of 40-60 mesh were placed in a reactor, and a 10 vol% H2 / Ar mixed gas with a flow rate of 30 mL / min was introduced for reduction for 40 min at 1 atm and 300°C. The reaction temperature was controlled at 200-360°C, and the temperature was controlled by a thermocouple. A mixture of H2O and CH3OH with a CH3OH / H2O molar ratio of 1 / 1.5 and a flow rate of 0.05 mL / min was injected into the vaporization chamber by a micropump, and the temperature was controlled at 200°C to completely evaporate the liquid into gas. The corresponding reaction space velocity (WHSV) was 42000 mL / h·g cat Then, Ar was introduced into the reactor at a flow rate of 30 mL / min to react. And its performance was evaluated.
[0056] The experimental results are as follows Figure 1 As shown, Example 1 successfully prepared a monoclinic ZrO2 carrier loaded with x wt.% CuO (x=1,3, 5, 7, 9, 11, 13); Figure 2 The prepared in Example 1 Figure 1 The monolayer dispersion threshold fitting curve obtained by XRD spectrum quantification; Figure 3 The X-ray diffraction (XRD) crystal phase structure analysis spectrum of the catalyst x wt.% CuO / t-ZrO2 obtained in Comparative Example 1; Figure 4 The comparative example 1 obtained Figure 3 Monolayer dispersion threshold fitting curve quantified from XRD spectrum. Figure 2 and Figure 4 It can be found that the monolayer dispersion threshold of monoclinic CuO on monoclinic ZrO2 carrier measured by XRD extrapolation method is more than twice that on tetragonal ZrO2 carrier. Figure 5 The XPS Cu 2p spectra measured for the catalysts obtained in Example 1 and Comparative Example 1 (x=1%, 3%, 5%) show that the peak area and dispersion of CuO on m-ZrO2 are larger for the same loading amount. Figure 6 The H2-TPR graphs of the catalysts obtained in Example 1 and Comparative Example 1 (x=1%, 3%, 5%) show that the reduction temperature of CuO on m-ZrO2 is always lower than that on t-ZrO2 for the same amount of CuO, indicating that the CuO on m-ZrO2 has a higher dispersion and is easier to reduce. Figure 2 , Figure 4 , Figure 5 , Figure 6 The results prove that when the crystal phase structure of the loaded metal oxide is the same as that of the carrier, it is more conducive to dispersion on the carrier surface. Figure 7, Figure 8 , Fig. 9 It shows that when the loading amount is the same, the comparison of CH3OH conversion rate and H2 yield of Example 4, Example 5 and Example 6 shows that the m-CuO / m-ZrO2 catalyst is significantly higher than the corresponding m-CuO / t-ZrO2 catalyst, which fully demonstrates that in the MTSR reaction, when the crystal phase structure of the carrier and the active component is the same, the active component is more evenly dispersed on the carrier, thereby showing better reaction performance.
Claims
1. A CuO / ZrO2 catalyst for hydrogen production from methanol reforming, characterized in that The ZrO2 carrier is monoclinic, and the catalyst is a CuO / ZrO2 catalyst loaded with monoclinic CuO.
2. The method for preparing a CuO / ZrO2 catalyst for hydrogen production from methanol reforming according to claim 1, characterized in that The following steps are involved: (1) Weigh a certain amount of ZrO(NO3)2 into a beaker, heat and stir in a 90°C water bath until it is completely dissolved; (2) Slowly add ammonia water to adjust the pH value of the solution to 12, stir and precipitate at room temperature for several hours; then wash the precipitate with deionized water until the total soluble solids (TDS) in the filtrate is < 20 ppm; (3) The product obtained in step (2) was then dried in an oven at 110° C. overnight, taken out and ground into powder; (4) calcining the product obtained in step (3) in a muffle furnace at 600 °C for 5 h at a heating rate of 2 °C / min to obtain a monoclinic ZrO2 carrier; (5) Prepare x wt.% CuO / ZrO2, x=1-5, by impregnation method. Dissolve a certain amount of Cu(NO3)23H2O(AR) in ionized water, and then add a corresponding mass of the monoclinic ZrO2 carrier obtained in step (4); stir the mixture at room temperature for 6 h, place it in a water bath at 80°C, stir and evaporate to dryness, place it in an oven at 110°C to completely dry it, and grind it; (6) The product obtained in step (5) was ground and placed in a muffle furnace at 450 °C and calcined at a heating rate of 2 °C / min for 4 h to obtain catalysts with different loading amounts of 1~5% CuO / ZrO2.
3. Use of the CuO / ZrO2 catalyst for hydrogen production from methanol reforming as claimed in claim 1 in hydrogen production from methanol steam reforming.
Citation Information
Patent Citations
Cu-based low-temperature water gas conversion catalyst under hydrogen rich reformed gas and preparation method thereof
CN102091617A
Catalyst for hydrogen production from steam reforming of methanol and preparation method thereof
CN105536790A
Catalyst for hydrogen production by methanol steam reforming and preparation method and application thereof
CN111068681A
Pd / ZnO-ZrO2 catalyst for hydrogen production by methanol steam reforming as well as preparation method and application of Pd / ZnO-ZrO2 catalyst
CN116251589A
Cu-Zr catalyst for steam reforming of methanol to prepare hydrogen and its prepn
CN1772378A